The golden lad [large type] : the haunting story of Quentin and Theodore Roosevelt - Burns, Eric (Thorndike Press large print biographies and memoirs, 2016)
Theodore Roosevelt is one of the most written-about presidents in American history, yet one poignant tale about this larger-than-life man hasn't been told. One of the causes he championed the hardest -- America's entry in to WWI -- took his youngest and favorite son in an air fight.